1983
DOI: 10.1113/jphysiol.1983.sp014477
|View full text |Cite
|
Sign up to set email alerts
|

The antagonism of amino acid‐induced excitations of rat hippocampal CA1 neurones in vitro.

Abstract: SUMMARY1. The effects ofthe ionophoretic application of a number ofexcitatory amino acids and antagonists to the dendrites of CAI neurones of rat hippocampal slices maintained in vitro were examined. Cells were excited by N-methyl-DL-aspartate (NMA), kainate, quisqualate, L-aspartate and L-glutamate; NMA was unique in causing cells to fire in bursts of repetitive discharges in contrast to the sustained firing seen with the other compounds.2. D-(-)-a-aminoadipate (DAA) and (±)-2-amino-5-phosphonovalerate (APV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(134 citation statements)
references
References 39 publications
13
121
0
Order By: Relevance
“…Schaeffer collateral LTP is considered a post-synaptic form of LTP in which activation of NMDA receptors leads to calcium entry, which then induces LTP [6,24,28]. We observed that APP/PS1KI mice with only one mutant PS1 allele, wildtype and PS1KI mice showed a normal LTP pattern at 6 months.…”
Section: Discussionmentioning
confidence: 79%
“…Schaeffer collateral LTP is considered a post-synaptic form of LTP in which activation of NMDA receptors leads to calcium entry, which then induces LTP [6,24,28]. We observed that APP/PS1KI mice with only one mutant PS1 allele, wildtype and PS1KI mice showed a normal LTP pattern at 6 months.…”
Section: Discussionmentioning
confidence: 79%
“…In all respects the mechanism is similar to that by which activation of mGluRs inhibits Ca2+ currents (Lester & Jahr, 1990). This potentiation may have a physiological role in forms of synaptic plasticity which are dependent on the activation of NMDA receptors, such LTP in the Schaffer collateral commissural pathway (Collingridge et al, 1983). In particular, it can explain how a mixture of IS,3R-ACPD and IR,3S-ACPD rapidly enhances STP (the initial phase of LTP) (McGuinness et al, 1991).…”
Section: Discussionmentioning
confidence: 85%
“…Activation of NMDA receptors and the resultant Ca 2+ influx are necessary for LTP induction in area CA1 (Collingridge et al 1983;Malenka et al 1988). Spatial enrichment may facilitate induction of LTP by increasing NMDA receptor currents or by enhancing neuronal membrane excitability.…”
Section: Glutamatergic Synaptic Currents and Spike Frequency Accommodmentioning
confidence: 99%